2005
DOI: 10.1021/jf050129y
|View full text |Cite
|
Sign up to set email alerts
|

Density and Microviscosity Studies of Palm Oil/Water Emulsions

Abstract: Electron paramagnetic resonance (EPR) and densitometry were used to measure the temperature- and rate-dependent formation of fat crystals in emulsion droplets in hardened palm kernel oil in water emulsions. The solid fat content in emulsions can be critical for the functionality of the emulsions in a wide variety of applications. Therefore, new and accessible methods are needed to monitor solid fat content in order to control the functional properties of these emulsions. EPR measurements showed that the microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The viscous properties of the continuous and dispersed phases in emulsions are expected to contribute to the overall emulsion rheology [1][2][3][4][5], but have not been independently investigated in situ to any appreciable extent due to lack of suitable methods. Rheological properties of emulsions are commonly characterized in the bulk using conventional macro-scale instruments such as controlled-shear or controlledstress rheometers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The viscous properties of the continuous and dispersed phases in emulsions are expected to contribute to the overall emulsion rheology [1][2][3][4][5], but have not been independently investigated in situ to any appreciable extent due to lack of suitable methods. Rheological properties of emulsions are commonly characterized in the bulk using conventional macro-scale instruments such as controlled-shear or controlledstress rheometers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the selection of an appropriate spin probe, ESR can be invaluable for studying materials containing fat and water ( , ). We have found that spin probes based on the 1,1,3,3-tetramethylisoindolin-2-yl structure (TMIO) are superior to commercially available spin probes such as TEMPO (): The main reasons are that there are fewer unresolved proton interactions and the molecules are rigid so that rapid interconversion does not increase the line width.…”
Section: Introductionmentioning
confidence: 99%